Long-Term Mortality following Acute Noninvasive Ventilation for Obesity-Related Respiratory Failure: A Retrospective Single-Centre Study - Aditya Krishnan; Paul Ellis; Pearlene Antoine-Pitterson; Amy Oakes; Bethany Jones; Alice Turner; Rahul Mukherjee (Canadian Respiratory Journal, 2023)
Introduction. Determinants of long-term mortality following acute hypercapnic respiratory failure have been extensively studied in patients with chronic obstructive pulmonary disease. However, respiratory failure due to obesity has not been studied to the same extent. This retrospective survey aims to identify whether admission pH is associated with long-term mortality in patients requiring acute noninvasive ventilation (NIV) for obesity-related respiratory failure (ORRF). Methods. Records from April 2013 to March 2020 were accessed from a NIV quality database at an acute teaching hospital. Adults with hypercapnic ORRF requiring acute NIV were included. pH data were grouped by threshold (pH≤ and >7.25) and correlated with time from presentation to death; multivariable analysis was performed using Cox proportional hazards. Results. A total of 277 acute NIV episodes were included. Two-year mortality was similar for patients in both pH categories. Univariable analysis identified pH ≤ 7.25 to increase risk of two-year mortality by 43%. However, multivariable analysis identified that pH was not a significant determinant of long-term mortality, although male sex, older age, and higher admission pCO2 increased the risk of death at two years by 76%, 3% per year of age, and 16% per 1 kPa of pCO2 increase, respectively. Conclusion. Severity of hypercapnia on admission, male sex, and older age are associated with worse two-year mortality in patients requiring acute NIV for ORRF. There is scope for further analyses including investigating the role of domiciliary NIV in ORRF patients.